Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

The Logic of masculinist protection: Reflections on the current security state - Young, Iris Marion (Signs, 2003)
Keywords: amériques; approches et analyses; discipline; discours dominant; histoire et politique; masculinité; patriarcat; philosophie; philosophie politique; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; sécurité nationale; thématiques; états-unis

La citoyenneté multiculturelle: une théorie libérale du droit des minorités - Kymlicka, Will (Éditions La Découverte ; Éditions du Boréal, 2001)
Les sociétés contemporaines deviennent de plus en plus des sociétés multiculturelles dans lesquelles les groupes minoritaires ethniques ou nationaux réclament une reconnaissance publique et les moyens de préserver leur identité culturelle. Une revendication qui n'est pas sans susciter des conflits qui menacent parfois l'unité territoriale des États. Pour Will Kymlicka, la réponse à cet enjeu devenu incontournable constitue aujourd'hui l'un des plus grands défis pour la démocratie. Son propos, dans ce livre devenu un classique de la théorie politique, est de défendre une nouvelle conception du statut et des droits des minorités culturelles.
Section: 357 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; citoyenneté; cours; discipline; discours dominant; europe; histoire et politique; inégalités; occident; phi4336; philosophie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

L'évidence de l'égalité des sexes : une philosophie oubliée du XVIIe siècle - Dorlin, Elsa (L'Harmattan, 2000)
Au XVIIe siècle, quatre philosophes, à quelques décennies d'intervalle, formulent en des styles très différents la thèse selon laquelle l'égalité entre les hommes et les femmes est une évidence, une vérité indiscutable. Marie de Gournay, Anna Maria Van Schurman, François Poullain de la Barre et Gabrielle Suchon, estiment que si les interdictions et les discriminations frappant les femmes perdurent, c'est que la querelle entre les défenseurs et les pourfendeurs du " Beau Sexe " est biaisée : les présupposés de la différence sexuelle rendent la question de l'égalité ou de l'inégalité des sexes indécidable.
Donné en lecture cours FEM1000: p.11-14 et 17-32
Keywords: 1600-1699; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; histoire des femmes*; histoire et politique; incontournable; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques